1987
DOI: 10.1002/j.1556-6676.1987.tb00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothering Adolescent Daughters: A Psychodynamic Perspective

Abstract: The psychology of motherhood during the daughter's adolescence is described in this article. Drawing on psychoanalytic and Jungian theoretical works as well as on research in adult development, the author describes (a) normal maternal development with an emphasis on the synergistic, maturational tasks of the mother and adolescent offspring; (b) maternal conflicts; and (c) counseling approaches that promote the mother's individuation and appropriate responses to her child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…This finding is also consistent with previous research that income poverty is associated with food insecurity (Poppendieck 1997), parental mental health (Conger et al 1992;McLoyd 1990), and adolescents' adjustment problems (Lehman and Koerner 2002;McLoyd and Wilson 1992). For example, adolescents' awareness of family economic hardship makes adolescents feel overburdened with responsibility for their family's needs (Bassoff 1987;Lehman and Koerner 2002), and engenders adjustment problems (e.g., Bassoff 1987;Lehman and Koerner 2002). A corollary finding is that the effects of SES are mediated through food insecurity, which points to the importance of the potential ameliorating effect of food assistance programs.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is also consistent with previous research that income poverty is associated with food insecurity (Poppendieck 1997), parental mental health (Conger et al 1992;McLoyd 1990), and adolescents' adjustment problems (Lehman and Koerner 2002;McLoyd and Wilson 1992). For example, adolescents' awareness of family economic hardship makes adolescents feel overburdened with responsibility for their family's needs (Bassoff 1987;Lehman and Koerner 2002), and engenders adjustment problems (e.g., Bassoff 1987;Lehman and Koerner 2002). A corollary finding is that the effects of SES are mediated through food insecurity, which points to the importance of the potential ameliorating effect of food assistance programs.…”
Section: Discussionsupporting
confidence: 91%
“…Rossi (1980) suggested that midlife parents' own developmental stress may contribute to strained family relationships and low morale during this time, by "feeding into adolescent's stress or complicating parental ability to cope with a growing child' (p. 142), while dealing with their own issues. Yet very little research focuses on the mother's perspective on raising an adolescent (Bassoff, 1987).…”
Section: The Midlife Mothermentioning
confidence: 99%
“…The developmental stages of adolescence and midlife both require the "enlargement of boundaries" (Bassoff, 1987). Mother and daughter are moving beyond the safety and security of the family to explore new facets of their lives.…”
Section: Self-definition: the Development Of Separate Identitiesmentioning
confidence: 99%
See 2 more Smart Citations